Nanoparticulate Carriers-Versatile Delivery Systems - Chawla R.; Rani V.; Mishra M. (My University, 2025)
Recently, significant efforts have been made on the development of biocompatible and biodegradable nanoparticulate carrier systems like polymeric nanoparticles, solid lipid nanoparticles, liposomes, etc. for delivery of drugs because of their potential benefits such as enhanced drug permeability, cell adhesion, cytotoxicity and cell attachment, improved bioavailability, reduced systemic toxicity, reduced local irritation, predictable gastric emptying, and improved pharmacokinetic behavior in comparison to conventional (monolithic) formulations. The sub-cellular and sub-micron size of nanoparticles facilitates trafficking and sorting into deep tissues through capillaries or fenestrations and also into different intracellular compartments such as macrophages, dendritic cells, etc. The delivery to target site and tissues can be controlled by engineering the polymer/lipid characteristics for their molecular weight, size, aqueous solubility, etc. The nanoparticulate carriers can be targeted both actively and passively. Conjugation with receptor-specific ligands results in active targeting with potential delivery of drugs to the target tissue. Autophagy is an example of passive targeting mechanism in which circulating cytoplasmic cells or organelles engulf the drug carriers (like in tuberculosis). Besides use of nanocarriers for delivery of drugs, they can also be used for delivery of DNA in gene therapy and administer proteins, peptides, and genes via peroral route. Thus, the nanoparticulate drug carriers have versatile applications in drug delivery and treatment of diseases. © 2021 Scrivener Publishing LLC.